Toward personalized dose-prescription in locally advanced non-small cell lung cancer: Validation of published normal tissue complication probability models. (September 2019) - Thor, M.; Deasy, Jo; Iyer, A.; Bendau, E.; Fontanella, A.; Apte, A.; Yorke, E.; Rimner, A.; Jackson, A.
Highlights: One AE2 and one RP2 model explained outcomes after RT in the investigated LA-NSCLC cohort. Reduce AE2: lower mean esophageal dose particularly when giving concurrent chemo-RT. Reduce RP2: lower mean lung dose particularly for old patients with pulmonary comorbidity. Model performance was modest, encouraging incorporation of unaccounted for information. Abstract: Purpose: To identify published normal tissue complication probability (NTCP) models suitable for patient-specific dose-prescription in locally advanced non-small cell lung cancer (LA-NSCLC) through in-house validation. Material and methods: From eight previously published candidate NTCP models (≥grade 2 acute esophagitis and radiation pneumonitis; AE2, RP2), patient-specific dose–responses were calculated using model variables and fractionation-corrected doses for 241 LA-NSCLC patients treated with chemo-IMRT to 50–80 Gy@1.8–2.0 Gy between 2004 and 2014 (AE2/RP2 rate: 50%/12%). A model was judged final if it significantly predicted AE2 or RP2 ( p  ≤ 0.05), was discriminative and well calibrated (AUC > 0.60; Hosmer–Lemeshow test p HL  > 0.05), which were assessed as the median over 1000 bootstrap samples. Results: Models for AE2 had superior discrimination to RP2 models (AUC = 0.63–0.65 vs. 0.51–0.65). The final AE2 model included mean esophageal dose and concurrent chemotherapy (AUC = 0.65; p  < 0.0001). The final RP2 model was a slightly adjusted version of the RP2 model with the best discrimination, and included age, mean lung dose, and pulmonary comorbidity (AUC = 0.73; p  < 0.0001). Conclusion: Of the eight investigated and published NTCP models, one model successfully described AE2 and one slightly adjusted model successfully described RP2 in the independent cohort. Estimates from these two NTCP models will, therefore, be considered internally when prescribing patient-specific doses in LA-NSCLC patients.